Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan Manufaktur (Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - Aprilawati, Niputu Irma; Ali, Karnila (Universitas Muhammadiyah Metro, 2022)
Irma Aprilawati, Ni Putu. 2021. The Effect of Profitability and Dividend Policy on the Value of Manufacturing Companies (In Manufacturing Companies Listed on the IDX). Thesis of Management Study Program, Faculty of Economics and Business, Muhammadiyah Metro University. (1) Dr. H. Febriyanto, S.E., M.M. (2) Nani Spetiana, S.E., M.M Company value is the price that prospective buyers are willing to pay if the company is sold. Company value is very important because it is a reflection of the company's performance that shows the company's prospects in the future which is also an indicator of the market assessment of the company as a whole. The purpose of this study is to determine together the effect of profitability (X1) and dividend policy (X2) on firm value (Y). This research was conducted on the Indonesia Stock Exchange by taking data through IDX. It taken 30 companies as the samples that registered in manufacturing companies in the period of 2018-2020 with the purposive sampling method. The analysis technique used is descriptive statistics. Based on the result of the analysis, it was found that profitability and dividend policy had an effect on firm value. Keywords: Profitability, Dividend Policy, Firm Value